Cloning and Stable Expression of cDNA Coding For Platelet Endothelial Cell Adhesion Molecule -1 (PECAM-1, CD31) in NIH-3T3 Cell Line - Hamed Salehi-Lalemarzi; Dariush Shanehbandi; Farzaneh Shafaghat; Hajar Abbasi-Kenarsari; Behzad Baradaran; Ali Akbar Movassaghpour; Tohid Kazemi (Tabriz University of Medical Sciences, 2015)
Purpose: PECAM-1 (CD31) is a glycoprotein expressed on endothelial and bone marrow precursor cells. It plays important roles in angiogenesis, maintenance and integration of the cytoskeleton and direction of leukocytes to the site of inflammation. We aimed to clone the cDNA coding for human CD31 from KG1a for further subcloning and expression in NIH- 3T3 mouse cell line. Methods: CD31 cDNA was cloned from KG1a cell line after total RNA extraction and cDNA synthesis. Pfu DNA polymerase-amplified specific band was ligated to pGEMT-easy vector and sub-cloned in pCMV6-Neo expression vector. After transfection of NIH-3T3 cells using 3 μg of recombinant construct and 6 μl of JetPEI transfection reagent, stable expression was obtained by selection of cells by G418 antibiotic and confirmed by surface flow cytometry. Results: 2235 bp specific band was aligned completely to human CD31 reference sequence in NCBI database. Transient and stable expression of human CD31 on transfected NIH-3T3 mouse fibroblast cells was achieved (23% and 96%, respectively) as shown by flow cytometry. Conclusion: Due to murine origin of NIH-3T3 cell line, CD31-expressing NIH-3T3 cells could be useful as immunogen in production of diagnostic monoclonal antibodies against human CD31, with no need for purification of recombinant proteins.